Penilaian Buku Teks Bahasa Indonesia Materi Teks Eksposisi Kelas X Kurikulum Merdeka Terbitan Erlangga - Jauhari, Falah (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
With the proliferation of textbooks in circulation, both from government and especially private publishers, many inadequacies in these texts have been discovered, both in terms of language, content and presentation. This of course has an impact on students and educators in the teaching and learning process. Assessment and analysis of textbooks is an urgency in combing through inappropriate textbooks. The object studied is the companion textbook Kombi: Class X Indonesian Competency, exposition text material. textbook. The research method used is descriptive qualitative. Assessment and analysis are based on indicators for each aspect with a score of 1-4 which is converted into a score of 1-100. The conclusion of the analysis results was that overall the six aspects assessed were, (1) synchronization between learning objectives flow (ATP), learning achievements (CP), materials, activities and learning assessments with a score of 91.7, (2) the truth of the material is in accordance with scientific principles with a score of 100, (3) strengthening the profile of pancasila with a score of 100, (4) presentation techniques with a score of 87.5, (5) linguistic aspects with a score of 100, (6) eligibility legality and norms are assessed based on surveys. Overall, it can be concluded that the textbooks analyzed in this research are suitable for use in the learning process. However, there needs to be improvements in the aspects of synchronization of ATP and CP, legal eligibility and norms, as well as presentation techniques so that the quality of the accompanying textbooks is even better.